2018
DOI: 10.22370/rbmo.2018.53.2.1291
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic activity of terrestrial <i>Streptomyces</i> sp. VITNK9 against Gram negative bacterial pathogens affecting the fish and shellfish in aquaculture

Abstract: Resumen.-Se realizaron un total de 72 aislamientos de actinomicetos morfológicamente diferentes a partir de muestras recolectadas en diferentes regiones de Vellore, Tamil Nadu, India y seleccionados por su actividad antibacteriana contra patógenos de peces y mariscos. Todos los aislamientos de actinomicetos fueron examinados para determinar la actividad antibacteriana por el método de rayas cruzadas contra los patógenos seleccionados de peces y mariscos incluyendo Aeromonas caviae, Aeromonas hydroplila, Edward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…48,49,119,122,141,142 Several studies have been demonstrated in fish and shellfish aquaculture using actinomycetes as antimicrobial sources. 41,59,60,68,99,101,107,111,123,128,131,133,134,137,[143][144][145][196][197][198][199][200] The different species of Actinomycetes used in aquaculture over the years have been summarized in Table 1.…”
Section: Actinomycetes As Antimicrobial and Anti-parasitic Agents In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…48,49,119,122,141,142 Several studies have been demonstrated in fish and shellfish aquaculture using actinomycetes as antimicrobial sources. 41,59,60,68,99,101,107,111,123,128,131,133,134,137,[143][144][145][196][197][198][199][200] The different species of Actinomycetes used in aquaculture over the years have been summarized in Table 1.…”
Section: Actinomycetes As Antimicrobial and Anti-parasitic Agents In ...mentioning
confidence: 99%
“…have been studied and found to kill the theronts and tomonts of Ichthyophthirius multifiliis and Cryptocaryon irritans 48,49,119,122,141,142 . Several studies have been demonstrated in fish and shellfish aquaculture using actinomycetes as antimicrobial sources 41,59,60,68,99,101,107,111,123,128,131,133,134,137,143–145,196–200 …”
Section: Actinomycetes As Antimicrobial and Anti‐parasitic Agents In ...mentioning
confidence: 99%
“…To discover natural products possessing antagonistic activity against fish pathogens, we isolated a new actinomycete strain, Streptomyces sp. strain VITNK9, from a terrestrial soil sample from Vellore, Tamil Nadu, India, using actinomycete isolation agar (AIA) plates ( 1 , 2 ). The strain had a smooth colony surface, an earthy odor, and a spiral spore formation, including aerial mycelia and substrate hyphae penetrating through agar, morphologies typical of Streptomycetes .…”
Section: Announcementmentioning
confidence: 99%
“…The strain had a smooth colony surface, an earthy odor, and a spiral spore formation, including aerial mycelia and substrate hyphae penetrating through agar, morphologies typical of Streptomycetes . The crude extract of the strain exhibited antimicrobial activity against several fish pathogens, implying that this strain can be an important resource of bioactive metabolites ( 1 ). Further, to obtain the genomic potential of VITNK9 to synthesize bioactive compounds, its genome was sequenced.…”
Section: Announcementmentioning
confidence: 99%
See 1 more Smart Citation